Polymorphism of the slow troponin t gene in Chinese elite long distance runners - Xu, C.; Hu, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Troponin T (TnT), the tropomyosin (Tm) binding subunit of the troponin complex, is an essential element in the Ca2+ signal transduction pathway for the thin filament-based regulation of striated muscle contraction. Slowskeletal, fast skeletal and cardiac muscle TnTs are encoded by different genes in the vertebrate. And the slow troponin T (sTnT) gene is located at chromosome 19q13.4 and composed of 15 exons. To our knowledge, no information is available concerning whether the SNP/C7761T of sTnT is associated with elite athletic status. Therefore, the purpose of the present study was to compare the frequency of the SNP between 123 elite long distance athletes and 204 healthy, sedentary controls. The investigation will also evaluate the association between sTnT gene SNP and elite endurance capacity. Methods All 327 subjects were unrelated Chinese people, and came from the Han population of northern China. The Han people constitute the majority (93.3%) of China`s 1.3 billion inhabitants, and generally reside in the northern areas. Chinese elite long distance athletes mainly come from North China, particularly Northeast China. DNA samples were obtained from two groups, controls and athletes. The control group consisted of 117 males and 87 females (mean age ± SEM, 21.2±1.9), all of them were healthy and sedentary. The athletes were 123 elite long distance athletes, 62 males and 61 females (mean age ± SEM, 23.2±3.1). Among those athletes, 58 were engaged in 5-Km, 34 were in 10-Km and 31 were marathon runners. Written informed consent was obtained from each subject prior to his/her inclusion to the study. Genomic DNA was extracted from lymphoblastoid cell lines using a kit (Promega, USA). The forward primer sequence was 5 - aaacacgaggcattgctg -3 , and reverse primer sequence was 5 - ctccttcttccgctgctc -3 . Amplification reaction was carried out in a volume of 20uL, containing 300ng genomic DNA, 0.2mM of each dNTP, 1.8mM MgCl2, 0.5pmol of each amplification primer and 1 units of HotStarTaq DNA polymerase (Takara, Japan). Reaction were heated at 95° for 5 min, subjected to 32 cycles of amplification ( 40s at 95°, 40s at 57°, 40s at 72°) before a final extension of 10 min at 72°. The length of the amplified fragment was 221bp. The PCR products were digested with 5 units of Eco 47 I restriction enzyme (Fermentas, Latbia) at 37° for 5h and run on a 3% agarose gel. All statistical analyses were completed with SPSS software for Windows 11.5 package. A 2 test was used to confirm whether genotype frequencies were in a Hardy-Weinberg equilibrium and to compare the SNP allele and genotype frequencies between athletes and controls. Genotype frequencies were also compared between controls and different distance athletes. Statistical significance was set at P<0.05. Results The genotype frequencies were in Hardy-Weinberg equilibrium (p>0.05). There was no difference in C7761T genotype frequencies between the controls and the athletes (p>0.05). There was no difference between the control and marathon athlete groups, or the 5Km and 10Km athlete groups (p>0.05). There was no difference between the controls and the international master athletes (p>0.05). The reasons for these results are not known, but might be related to the SNP, which is in the gene intron region. The SNP within a gene intron region may not affect gene function. Conclusions Our findings suggested that C7761T might have no association with the capacity of elite endurance performance. In view of the important functions of sTnT in skeletal muscle contraction, further study should be conducted on other polymorphisms of the sTnT gene in Chinese elite long distance runners. Further investigation would identify if there is an association between the polymorphisms of sTnT gene and elite aerobic ability.